2020
DOI: 10.2147/copd.s268110
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Chronic Obstructive Pulmonary Disease and its Associated Factors in Nepal: Findings from a Community-based Household Survey</p>

Abstract: Background: Despite chronic obstructive pulmonary disease (COPD) being the commonest non-communicable disease in Nepal, there is limited research evidence estimating the spirometry-based burden of COPD. This study aims to estimate the prevalence of COPD and its correlates through a community-based survey in Pokhara Metropolitan City, a semiurban area of Western Nepal. Methods: A cross-sectional household survey was conducted among 1459 adults ≥40 years. COPD was defined according to the Global Initiative for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 34 publications
5
35
1
1
Order By: Relevance
“…Ghaffar et al found that in South Asian countries, including Nepal, poorer people burn wood as fuel in their homes, especially in winter, which may likely increase the indoor air pollution and contribute to the burden of COPD [ 12 ]. These results are in line with the results published from Nepal and Sri Lanka that suggest a significant burden of COPD in the non-smoker population [ 2 , 9 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ghaffar et al found that in South Asian countries, including Nepal, poorer people burn wood as fuel in their homes, especially in winter, which may likely increase the indoor air pollution and contribute to the burden of COPD [ 12 ]. These results are in line with the results published from Nepal and Sri Lanka that suggest a significant burden of COPD in the non-smoker population [ 2 , 9 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to the World Health Organization (WHO), the prevalence of smoking is 56.5% in men and 19.5% in women. However, the prevalence of COPD appears to be higher among Nepali women than men [ 2 , 3 ]. These high numbers from Nepal could be attributed to the fact that, in Nepal, more than 85% of households (98% in rural areas) are rural dwellers and still rely on biomass fuel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Due to the higher smoking rates and aging of population, its prevalence and number of deaths are still increasing. 4,5 The most common cause of COPD is smoking, 6 while other factors can also contribute to the onset of this disease, mainly including secondhand smoke, pollution and fumes, age, infections, occupational dusts/chemicals, untreated asthma and genetic factors such as deficiency of alpha-1 antitrypsin. 7 The possible pathogenesis of COPD is strongly linked to chronic inflammatory responses due to the activation of many cell types such as myeloid cells and epithelial cells in response to possible irritants (such as those released from tobacco or polluted air) in the lung of genetically susceptible individuals.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“… 3 Due to the higher smoking rates and aging of population, its prevalence and number of deaths are still increasing. 4 , 5
Figure 1 Prevalence of chronic obstructive pulmonary disease (COPD) in selected countries, 1990–2019. Data are from the Global Burden of Disease.
…”
Section: Introductionmentioning
confidence: 99%